Features of the Treatment for the Syndrome of Dehydration in Infants and Older Children, Newborns: Fundamentals of Parenteral Rehydration - V.I. Snisar; O.Yu. Sorokina; A.V. Bolonska; S.V. Yehorov (Zaslavsky O.Yu., 2016)
In pediatric practice, the syndrome of dehydration is quite common. In children, the most likely cause of the fluid loss is gastroenteritis syndrome and diarrhea of various origins. These causes are often associated with diarrhea and vomiting that results in the loss of water and electrolytes in various proportions. In contrast to the treatment of critical conditions, such as hypovolemic and septic shock, there is no standardized approach to the correction of mild to moderate syndrome of dehydration. The role of oral rehydration in the prehospital and hospital stage is significantly underestimated. This article is a sign of interest in the unification of approaches to the treatment of such conditions, makes it possible to get acquainted with a generalized view of the treatment and prevention of a variety of adverse reactions on the background of oral and/or parenteral rehydration. Our survey reminds the practitioner about the features of dehydration syndrome in children of different age groups, the importance of taking into account the pathogenesis of various types of dehydration during the diagnosis, demonstrates the importance of knowledge in the field of infusion media in the context of the therapy balanced in terms of the volume and components, as well as considers the target fluid spaces of the body under pathological losses. We investigate the concept of physiological infusion solution on the basis of evidence-based medicine. This review is advisory, it is based both on the national experience in the treatment of the syndrome of dehydration and foreign resources analysis.